2018
DOI: 10.1163/22134808-00002596
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Sensitivity to Illusory Target Motion With or Without Secondary Tasks

Abstract: Older individuals seem to find it more difficult to ignore inaccurate sensory cues than younger individuals. We examined whether this could be quantified using an interception task. Twenty healthy young adults (age 18-34) and twenty-four healthy older adults (age 60-82) were asked to tap on discs that were moving downwards on a screen with their finger. Moving the background to the left made the discs appear to move more to the right. Moving the background to the right made them appear to move more to the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 54 publications
4
20
1
Order By: Relevance
“…Also consistent with the reweighting explanation are recent findings on changes in induced motion in older observers ( de Dieuleveult, Brouwer, Siemonsma, van Erp & Brenner, 2018 ; de Dieuleveult, Perry, Siemonsma, Brouwer & van Erp, 2019 ). Induced motion is commonly experienced as illusory movement of an object in the opposite direction to the movement of its surrounding background ( Duncker, 1929 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Also consistent with the reweighting explanation are recent findings on changes in induced motion in older observers ( de Dieuleveult, Brouwer, Siemonsma, van Erp & Brenner, 2018 ; de Dieuleveult, Perry, Siemonsma, Brouwer & van Erp, 2019 ). Induced motion is commonly experienced as illusory movement of an object in the opposite direction to the movement of its surrounding background ( Duncker, 1929 ).…”
Section: Discussionsupporting
confidence: 80%
“…Induced motion is commonly experienced as illusory movement of an object in the opposite direction to the movement of its surrounding background ( Duncker, 1929 ). Dieuleveult et al (2018) argued that the stronger influence of the background motion in older participants was due to lower sensitivity in proprioceptive and vestibular systems and thus greater dependence on visual information.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, Berard et al (2012) found that old age affects the ability to down-regulate the influence of such visual information in a walking task. In an original experiment (de Dieuleveult et al, 2018), we investigate whether this effect generalizes to another paradigm, namely the paradigm of Brouwer et al (2003) that used the Duncker illusion (or induced motion) (Duncker, 1929). The object appears to move differently due to movement in its surrounding (Soechting et al, 2001; Zivotofsky, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…OA’s interception points (called taps) were more deviated to the left for a right background motion and to the right for a left background motion than those of YA. These results could reflect a reduced ability to ignore or downregulate irrelevant sensory information and/or a greater reliance on vision because of unreliable somatosensory and proprioceptive systems (de Dieuleveult et al, 2018). If the ability to ignore or downregulate irrelevant sensory information is indeed reduced in OA, our interception task may be a useful tool to diagnose sensory integration problems that could underlie (future) problems in ADL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation